(untitled) (Marketing Journal, 2024)
This work is devoted to the development and improvement of the methodology for improving export competence of small business and private enterprise. In the present context of globalization and integration of economies, the relevance of this topic is indisputable, since exports are a key element of sustainable development and business competitiveness. The work examines the main aspects affecting the success of export operations among small businesses and private entrepreneurs, and analyses existing methods and suggests new approaches to improve them.